2019
DOI: 10.1259/bjr.20180414
|View full text |Cite
|
Sign up to set email alerts
|

Iodine load reduction in dual-energy spectral CT portal venography with low energy images combined with adaptive statistical iterative reconstruction

Abstract: Objective: To study the application of using low energy images combined with adaptive statistical iterative reconstruction (ASiR) in dual-energy spectral CT portal venography (CTPV) to reduce iodine load. Methods: 41 patients for CTPV were prospectively and randomly divided into two groups. Group A ( n = 21) used conventional 120 kVp scanning protocol with contrast dose at 0.6 gI/kg while group B ( n = 20) used dual-energy spectral imaging with reduced contrast dose at 0.3 gI/kg. The 120 kVp images in Group A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Many efforts have been made to reduce the amount of contrast media as much as possible while maintaining portal vein image quality [ 17 , 20 ]. Han et al [ 21 ] used lower monoenergetic images combined with adaptive statistical iterative reconstruction (ASiR) in dual-energy spectral CT to reduce the iodine amount in CT portal venography (CTPV). They found that 50 keV images with ASiR reconstruction could reduce the total iodine amount by 52% while maintaining good image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to reduce the amount of contrast media as much as possible while maintaining portal vein image quality [ 17 , 20 ]. Han et al [ 21 ] used lower monoenergetic images combined with adaptive statistical iterative reconstruction (ASiR) in dual-energy spectral CT to reduce the iodine amount in CT portal venography (CTPV). They found that 50 keV images with ASiR reconstruction could reduce the total iodine amount by 52% while maintaining good image quality.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the studies reviewed [19][20][21][22][23]27,28,34,35,39,40 , a wide range of net iodine doses used in the different tests is described, in milligrams iodine per weight (mgI/kg), from 280 to 600 mgI/kg using SECT equipment, and when performing the same examination with DECT technology, said dose is reduced to a range of 140-510 mgI/kg.…”
Section: Reduction Of the Icm Dose In Dect Equipmentmentioning
confidence: 99%
“…En algunos de los estudios revisados [19][20][21][22][23]27,28,34,35,39,40 se describe un amplio rango de dosis de yodo neto utilizadas en los diferentes exámenes, en miligramos yodo por peso (mgI/kg), desde 280 hasta 600 mgI/kg usando equipos de SECT, y al momento de realizar el mismo examen con tecnología DECT se disminuye dicha dosis hasta un rango de 140 a 510 mgI/kg.…”
Section: Disminución De La Dosis De Mcy En Los Equipos De Dectunclassified